2023
DOI: 10.1021/acs.jpcc.3c02247
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Photocatalytic Hydrogen Production of Y5 and Y6 Nanoparticles

Abstract: Utilization of solar energy in organic semiconductors relies on complicated photophysical processes due to the strong electron–hole interactions. To gain a better understanding of these processes and their effect on the photocatalytic performance of non-fullerene acceptors (NFAs) within nanoparticles (NPs), we compared the excited-state dynamics and photocatalytic hydrogen production activity of two NFA-based NPs, Y5 and Y6. Our results show that under LED light irradiation, Y5 NPs exhibit 14 times better hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As shown in Figure 4c,d, CCAP exhibits the largest semicircle in the Nyquist plot and the lowest transient photocurrent density among all CAPs, suggesting that the linear configuration was beneficial for accelerating the interfacial charge transfer and charge separation than cross‐linked structure. Additionally, as evidenced by the photoluminescence (PL) spectra (Figure S16, Supporting Information), CCAP also displayed a stronger quenching intensity than LCAP‐1 and LCAP‐2 with/without the addition of the hole scavenger (EDTA‐2Na), confirmed that the separation of electron–holes was more favored in linear configuration, [ 42 ] which explained the enhanced H 2 O 2 production property in linear configuration kinetically. The molecular electrostatic potential (MESP), dipole moment calculation, and water contact angle were employed to investigate the immanent cause of decreased photocatalysis property in cross‐linked structure.…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Figure 4c,d, CCAP exhibits the largest semicircle in the Nyquist plot and the lowest transient photocurrent density among all CAPs, suggesting that the linear configuration was beneficial for accelerating the interfacial charge transfer and charge separation than cross‐linked structure. Additionally, as evidenced by the photoluminescence (PL) spectra (Figure S16, Supporting Information), CCAP also displayed a stronger quenching intensity than LCAP‐1 and LCAP‐2 with/without the addition of the hole scavenger (EDTA‐2Na), confirmed that the separation of electron–holes was more favored in linear configuration, [ 42 ] which explained the enhanced H 2 O 2 production property in linear configuration kinetically. The molecular electrostatic potential (MESP), dipole moment calculation, and water contact angle were employed to investigate the immanent cause of decreased photocatalysis property in cross‐linked structure.…”
Section: Resultsmentioning
confidence: 88%
“…This effect can have a strong influence on the photovoltaic response of these materials since the reduction of the exciton binding energy opens the possibility of using D/A blends with a lower driving force, an excellent strategy to increase the V OC of OSCs . The reduction in excitonic effects also offers advantages in utilizing these molecules for applications in photocatalytic hydrogen production via solar water splitting. , …”
Section: Resultsmentioning
confidence: 99%
“…86 The reduction in excitonic effects also offers advantages in utilizing these molecules for applications in photocatalytic hydrogen production via solar water splitting. 87,88 To clarify the reasons behind the decrease of the exciton binding energy, we presented the energies of the NFA's lowlying electronic excited states in Figure 6b. The corresponding spatial distribution of the frontier orbitals associated with these excited states is illustrated in Figure S4.…”
Section: Structural Modificationsmentioning
confidence: 99%
“…Compared to non-OPV-derived, unprocessable, organic materials, which commonly show EQEs exceeding 10%, the efficiency of the above-mentioned materials for sacrificial hydrogen production is uniformly low. Even the state of the art Y series of NFAs does not have maximum EQEs that can exceed 1% . This is perhaps unsurprising when one takes into account that these materials are not designed to be single-semiconductor systems.…”
Section: Opv Materials For Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“… 42 Typically, the fluorinated molecule, Y6, outperforms the nonhalogenated end group analogue, Y5 (both shown in Figure 4 ), in binary OPV devices due a combination of red-shifted absorption, closer and more slip-stacked π–π interactions, and reduced reorganization energies. 43 However, when nanoparticles of Y6 and Y5 were recently tested for photocatalytic proton reduction, 44 it was found that Y5 had a HER more than 14 times higher than Y6. The authors ascribe this primarily to formation of a longer lived triplet exciton in the Y5 material, but the increased driving force for proton reduction by the more shallow LUMO could also play a role.…”
Section: Opv Materials For Photocatalytic Hydrogen Productionmentioning
confidence: 99%